2014
DOI: 10.1007/s12098-014-1630-1
|View full text |Cite
|
Sign up to set email alerts
|

Feeding Problems Among Children with Autism in a Clinical Population in India

Abstract: These findings underscore the need for mandatory assessment of FP in children with developmental disabilities, and if present, they need to be addressed with multimodal-multidisciplinary interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 15 publications
0
19
1
2
Order By: Relevance
“…Thus, oral sensory processing, and possibly oral hypersensitivities, may be significantly related to food refusal behaviours, although replication and future research is needed. Furthermore, Crasta et al (2014) found significant associations between food refusal and other important sensory subscales, including the modulation of sensory input affecting emotion levels, a finding supported by Shamaya et al (2017) who found significant associations between food refusal and modulation of visual input affecting emotion levels. Both studies highlight the importance of approaching food refusal as a multi-dimensional sensory experience, related to differences across sensory, motor and emotional domains.…”
Section: Food Refusalmentioning
confidence: 65%
See 3 more Smart Citations
“…Thus, oral sensory processing, and possibly oral hypersensitivities, may be significantly related to food refusal behaviours, although replication and future research is needed. Furthermore, Crasta et al (2014) found significant associations between food refusal and other important sensory subscales, including the modulation of sensory input affecting emotion levels, a finding supported by Shamaya et al (2017) who found significant associations between food refusal and modulation of visual input affecting emotion levels. Both studies highlight the importance of approaching food refusal as a multi-dimensional sensory experience, related to differences across sensory, motor and emotional domains.…”
Section: Food Refusalmentioning
confidence: 65%
“…Furthermore, Crasta et al. (2014) found significant associations between food refusal and other important sensory subscales, including the modulation of sensory input affecting emotion levels, a finding supported by Shamaya et al. (2017) who found significant associations between food refusal and modulation of visual input affecting emotion levels.…”
Section: Mealtime Behavioursmentioning
confidence: 77%
See 2 more Smart Citations
“…It was difficult to draw a conclusion about the relation of feeding problems in children with the ASD and severity of autism due to the conflicting reports. Some studies suggesting that it is related to children with autism [4] while others refute this claim [48].…”
Section: Discussionmentioning
confidence: 99%